An Exploratory Study of Students’ Mathematical Problem-Solving Ability Based on Wankat and Oreovocz Theory - Rahayu, Dini; Hsien, Tan Wen (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to explore students’ mathematical problem-solving ability based on the Wankat and Oreovocz theory by identifying how students perform across each stage of the problem-solving process in order to provide a comprehensive description of their abilities. Methodology: This study employed a qualitative descriptive approach using purposive sampling, involving six students from class VII E at SMP Negeri 19 Bandar Lampung. Data were systematically collected through observation, written essay tests, and semi-structured interviews, and analyzed using data reduction, data display, and conclusion drawing with triangulation techniques for validation purposes. Main Findings: The results show that most students achieved high problem-solving ability, with 59.26% in the excellent category and 25.93% in the good category. Students performed best at the motivation stage (“I Can”) but showed lower performance in planning, evaluation, and generalization stages. High-performing students completed all stages systematically, while lower-performing students experienced difficulties beyond initial stages, especially in selecting appropriate strategies and verifying solutions. Novelty/Originality of this study: This study offers a detailed stage-based analysis of students’ mathematical problem-solving ability using the Wankat and Oreovocz framework, focusing on students’ actual performance rather than instructional strategies. It provides new insights into specific difficulties at each stage, particularly in planning, and contributes to advancing knowledge on how structured problem-solving frameworks can be applied to analyze students’ cognitive processes.